2000
DOI: 10.1103/physrevb.61.6654
|View full text |Cite
|
Sign up to set email alerts
|

Glassy dynamics in supercooled-liquid and glassy ethanol: A molecular dynamics study

Abstract: Static and dynamic properties of supercooled liquid and glassy ethanol are evaluated from computer molecular dynamics simulations and compared with experimental data whenever possible. In particular, a comparison with recent neutron-scattering data is done and the results indicate that the relatively simple model here employed is able to reproduce most of the observed features, at least on semiquantitative grounds. Special attention is paid to monitor how the relevant dynamical properties change through the gl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
35
1
9

Year Published

2003
2003
2020
2020

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 29 publications
(46 citation statements)
references
References 46 publications
1
35
1
9
Order By: Relevance
“…Second, our simulation results suggest that propagation of longitudinal excitations in the ODC at low temperatures takes place beyond frequencies characteristic of the "boson peak" ͑BP͒ which for this material appears at Ϸ2 meV. 4,15 Such frequencies are, however, confined to values not far in excess of that of the BP at high temperatures. As far as identification of the prime entities responsible for scattering of acoustic phonons, low-energy torsional librations about the C-C bond 14 are deemed to be the main contributors to such processes.…”
Section: ͑1͒mentioning
confidence: 90%
See 2 more Smart Citations
“…Second, our simulation results suggest that propagation of longitudinal excitations in the ODC at low temperatures takes place beyond frequencies characteristic of the "boson peak" ͑BP͒ which for this material appears at Ϸ2 meV. 4,15 Such frequencies are, however, confined to values not far in excess of that of the BP at high temperatures. As far as identification of the prime entities responsible for scattering of acoustic phonons, low-energy torsional librations about the C-C bond 14 are deemed to be the main contributors to such processes.…”
Section: ͑1͒mentioning
confidence: 90%
“…Since we are here interested in the behavior of acoustic phonons, the relevant mass is the molecular mass M Ϸ 46 amu and d min Ϸ 5 Å, as determined from the first intermolecular peak in the experimental radial distributions. 15 At T =5 K T Ϸ 1 Å which ensures that results pertaining to whole-molecule motions are not expected to exhibit large quantum behaviors. On the other hand, the strength of anharmonic effects was previously measured from the temperature ͑see Criado et al 4 ͒ and volume ͑see Fischer et al 4 ͒ dependencies of the phonon frequencies.…”
Section: ͑1͒mentioning
confidence: 99%
See 1 more Smart Citation
“…Data pertaining to the temperature dependence of a, as well the value for ␥, have been explicitly measured 28,29 and the Debye temperature was calculated from low temperature specific heat and yields ⍜ D = 229 K. 30 A calculation leaving A and B as adjustable parameters yields a good account of data for the ODC crystal between 50 and 90 K. The parameter values are A = 1.12ϫ 10 6 W m 2 K 2 and B = −1.215ϫ 10 6 W m 2 K 2 . Notice that both terms in Eq.…”
Section: Methodsmentioning
confidence: 99%
“…The complexity of the problem can be reduced by regarding simpler systems in which only orientational degrees of freedom are frozen giving rise to orientational glasses or glassy crystals by supercooling the orientationally disordered (or plastic) phases. [17][18][19] The complexity can be further reduced analyzing systems in which the orientational disorder is due to the existence of an intrinsic statistical disorder involving the site occupancy of several atoms of the molecular entities. In some of these cases, it has been demonstrated that the main glass features show up, pointing out the relevance of the orientational degrees of freedom as far as the glass properties are considered.…”
Section: Introductionmentioning
confidence: 99%